Improved bootstrap confidence intervals for the process capability index Cpk. Issue 10 (2nd October 2020) - Park, Chanseok; Dey, Sanku; Ouyang, Linhan; Byun, Jai-Hyun; Leeds, Mark
Abstract: The process capability index, Cpk, is a useful tool for assessing the capability of a manufacturing process. There exist three well-known confidence intervals for the process capability index. These intervals are based on the standard bootstrap, the percentile bootstrap and the bias-corrected percentile bootstrap, respectively. We propose three variants of these bootstrap confidence intervals where each of the three intervals are modified in a particular way. Extensive Monte Carlo simulations are carried out and the results indicate that the three proposed bootstrap methods are generally preferred over the corresponding original schemes.